Asymmetric Acceptors with Fluorine and Chlorine Substitution for Organic Solar Cells toward 16.83% Efficiency. (29th April 2020) - Liu, Tao; Zhang, Youdi; Shao, Yiming; Ma, Ruijie; Luo, Zhenghui; Xiao, Yiqun; Yang, Tao; Lu, Xinhui; Yuan, Zhongyi; Yan, He; Chen, Yiwang; Li, Yongfang
Abstract: Small‐molecule acceptors (SMAs)‐based organic solar cells (OSCs) have exhibited great potential for achieving high power conversion efficiencies (PCEs). Meanwhile, developing asymmetric SMAs to improve photovoltaic performance by modulating energy level distribution and morphology has drawn lots of attention. In this work, based on the high‐performance SMA (Y6), three asymmetric SMAs are developed by substituting the fluorine atoms on the terminal group with chlorine atoms, namely SY1 (two F atoms and one Cl atom), SY2 (two F atoms and two Cl atoms), and SY3 (three Cl atoms). Y6 (four F atoms) and Y6‐4Cl (four Cl atoms) are synthesized as control molecules. As a result, SY1 exhibits the shallowest lowest unoccupied molecular orbital energy level and the best molecular packing among these five acceptors. Consequently, OSCs based on PM6:SY1 yield a champion PCE of 16.83% with an open‐circuit voltage ( V OC ) of 0.871 V, and a fill factor (FF) of 0.760, which is the best result among the five devices. The highest FF for the PM6:SY1‐based device is mainly ascribed to the most balanced charge transport and optimal morphology. This contribution provides deeper understanding of applying asymmetric molecule design method to further promote PCEs of OSCs. Abstract : Three asymmetric small‐molecule acceptors are developed by changing the fluorine atoms on the terminal group of Y6 to chlorine atoms, namely SY1, SY2, and SY3, with Y6, and Y6‐4Cl are utilized as the reference. Organic solar cells based on the PM6:SY1 blend demonstrate a champion power conversion efficiency of 16.83%. This work can provide a deeper and more comprehensive understanding of applying the asymmetric molecule design method.